ZnS photocatalytic nano material as well as preparation method and application thereof

Through a simple preparation method, ZnS photocatalytic nanomaterials with a microsphere structure assembled with three-dimensional nanoparticles were prepared, which solved the problem of poor photocatalytic effect of existing ZnS materials under sunlight, achieved efficient degradation of tetracycline, and had good controllability and industrial prospects.

CN119733532AActive Publication Date: 2025-04-01BCEG ENVIRONMENTAL REMEDIATION CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411898023.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-01
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing ZnS materials have poor photocatalytic effects under sunlight, their preparation process is complicated and complex, and they require template agents and have poor controllability, which limits their promotion and practical application.

Method used

By obtaining a mixed solution of zinc organic acid salt, triethylenetetramine and solvent, dissolving the sulfur source in the mixed solution, and carrying out hydrothermal reaction to prepare ZnS photocatalytic nanomaterials. The material has a unique micro-spherical structure assembled by three-dimensional nanoparticles, uniform in size and good dispersion.

Benefits of technology

The efficient photocatalytic degradation of tetracycline of ZnS nanomaterials is achieved, with an efficiency much higher than that of existing ZnS materials. The preparation method is simple to operate, no template agent is required, and has good controllability and industrial prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733532A_ABST
    Figure CN119733532A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photocatalytic nano materials, in particular to a ZnS photocatalytic nano material and a preparation method and application thereof. The preparation method of the ZnS photocatalytic nano material comprises the following steps: obtaining a mixed solution of organic acid zinc salt, triethylene tetramine and a solvent; and dissolving a sulfur source in the mixed solution to obtain a reaction precursor solution, and carrying out a reaction to prepare the ZnS photocatalytic nano-material. The ZnS nano-material prepared by the method has a unique micron spherical structure assembled by three-dimensional nano-particles, and is uniform in size, good in dispersity and excellent and stable in photocatalytic performance. Meanwhile, the preparation method provided by the invention is simple and convenient to operate, free of a template agent, rapid in preparation, rich in raw material source, low in cost and environment-friendly, and has a wide industrial prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalytic nanomaterials, and in particular to a ZnS photocatalytic nanomaterial and a preparation method and application thereof. Background Art

[0002] As a typical wide bandgap semiconductor material, ZnS is one of the most active compounds among metal sulfides. Due to its superior performance, it is widely used in sensors, photodetectors, photocatalysis and other fields. In the field of photocatalysis, many studies have shown that the catalytic performance of materials is closely related to their morphology, size and crystal form. Therefore, the controllable preparation of the morphology, size and crystal form of ZnS nanomaterials has become an important way to regulate their performance.

[0003] However, although there are many methods for preparing ZnS nanomaterials with different morphologies, sizes and crystal forms, most of them have the disadvantages of complicated preparation process, the need for templates, poor controllability and low yield. In addition, the ZnS materials prepared on the market generally respond to light in the ultraviolet region. Under the irradiation of sunlight (simulated sunlight), the photocatalytic performance is not ideal and needs to be improved. These factors greatly limit the promotion and practical application of ZnS nanomaterials. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of existing ZnS materials, such as poor photocatalytic effect under sunlight irradiation, complicated preparation process, requirement of template, and poor controllability, so as to provide a ZnS photocatalytic nanomaterial and its preparation method and application to solve the above problems.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a ZnS photocatalytic nanomaterial, comprising:

[0007] obtaining a mixed solution of organic acid zinc salt, triethylenetetramine and solvent;

[0008] The sulfur source is dissolved in the mixed solution to obtain a reaction precursor solution and a reaction is carried out to prepare the ZnS photocatalytic nanomaterial.

[0009] Preferably, the organic acid zinc salt comprises zinc acetate;

[0010] and / or, the sulfur source comprises thiourea;

[0011] And / or, the mixed solution also includes sodium tartrate;

[0012] and / or, the volume ratio of the solvent to triethylenetetramine is (4-1):1, preferably (3-2):1;

[0013] And / or, the solvent is water or an alcohol aqueous solution; preferably, the alcohol aqueous solution includes an ethanol aqueous solution; more preferably, the concentration of ethanol in the ethanol aqueous solution is ≤25 vol%.

[0014] Preferably, based on the total amount of triethylenetetramine and the solvent being 40 ml, the amount of sodium tartrate used is 0.05-0.2 g.

[0015] Preferably, the amount of the organic acid zinc salt is 0.5-0.8 g based on the total amount of triethylenetetramine and the solvent being 40 ml;

[0016] And / or, the mass ratio of the organic acid zinc salt to the sulfur source is (0.5-0.8): (0.1-0.3);

[0017] And / or, the process of obtaining the mixed solution includes: dissolving the organic acid zinc salt in a solution of triethylenetetramine and a solvent to obtain the mixed solution.

[0018] Preferably, the reaction is a hydrothermal reaction or a solvothermal reaction;

[0019] And / or, the reaction temperature is 130-160°C;

[0020] And / or, the reaction duration is 10-14h;

[0021] And / or, during the process of obtaining the mixed liquid, stirring is also performed;

[0022] And / or, during the process of obtaining the reaction precursor solution, stirring is also performed;

[0023] And / or, after the reaction, cooling, washing and drying are further performed.

[0024] Preferably, the stirring speed is 150-500r / min;

[0025] And / or, the stirring treatment lasts for 20-40 minutes;

[0026] And / or, during the washing process, water and anhydrous ethanol are respectively used for centrifugal washing 4-6 times;

[0027] And / or, the drying temperature is 50-70°C;

[0028] And / or, the duration of the drying treatment is ≥ 12 h.

[0029] Preferably, the rotation speed of the centrifugal washing is 4000-6000r / min;

[0030] And / or, the duration of the centrifugal washing is 2-5 min.

[0031] In a second aspect, the present invention further provides a ZnS photocatalytic nanomaterial, which is prepared by the above-mentioned method for preparing the ZnS photocatalytic nanomaterial.

[0032] In a third aspect, the present invention also provides the use of the above-mentioned ZnS photocatalytic nanomaterial in photocatalytic degradation of organic pollutants in water.

[0033] Preferably, the organic pollutant is an antibiotic; optionally, the antibiotic comprises tetracycline.

[0034] The technical solution of the present invention has the following advantages:

[0035] 1. A method for preparing a ZnS photocatalytic nanomaterial, comprising: obtaining a mixed solution of an organic acid zinc salt, triethylenetetramine and a solvent; dissolving a sulfur source in the mixed solution to obtain a reaction precursor solution and reacting to obtain a ZnS photocatalytic nanomaterial. The ZnS nanomaterial prepared by the present invention has a unique micron-spherical structure of three-dimensional nanoparticle assembly, uniform size, good dispersibility, excellent and stable photocatalytic performance, and a photocatalytic degradation efficiency of tetracycline that is much higher than that of existing ZnS materials (within 300 minutes under simulated sunlight, the ZnS nanomaterial of the present invention can degrade 10 mg / L tetracycline by more than 44.2%, and can even reach 80.5%, while the degradation rate of tetracycline by existing ZnS materials on the market is only 25.5%). At the same time, the preparation method provided by the present invention is simple to operate, does not require a template agent, and has good controllability (the ZnS nanomaterial prepared by the present invention has high purity and crystallinity, and few impurities), is fast to prepare, has abundant raw material sources, is low in cost, is environmentally friendly, and has broad industrial prospects.

[0036] 2. When the ZnS photocatalytic nanomaterial of the present invention is used in the photocatalytic degradation of organic pollutants in water, it is different from the existing composite materials of ZnS nanomaterials and other carriers (for example, carbon materials). The present invention can have the performance of efficient photocatalytic degradation of tetracycline under sunlight, has broad application prospects in the field of water treatment, and at the same time provides a strong theoretical basis for the practical application of wide bandgap semiconductor nanomaterials under natural light. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1This is the XRD pattern of the ZnS photocatalytic nanomaterial prepared in Example 1 of the present invention;

[0039] Figure 2 This is a SEM (scale is 2 μm) image of the ZnS photocatalytic nanomaterial prepared in Example 1 of the present invention;

[0040] Figure 3 This is a SEM (scale is 500 nm) image of the ZnS photocatalytic nanomaterial prepared in Example 1 of the present invention;

[0041] Figure 4 The graph shows the photocatalytic degradation of tetracycline by the ZnS photocatalytic nanomaterial prepared in Example 1 of the present invention, the ZnS (commercially available) material, and the blank control group. DETAILED DESCRIPTION

[0042] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0043] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0044] Example 1

[0045] This embodiment provides a method for preparing a ZnS photocatalytic nanomaterial, and the specific steps are as follows:

[0046] 1) Obtaining a mixed solution: Under room temperature, weigh 0.658 g of zinc acetate dihydrate and 0.1 g of sodium tartrate, respectively, and dissolve them in 40 ml of an aqueous solution of triethylenetetramine (the volume ratio of water to triethylenetetramine is 3:1), and then stir them at a constant speed (300 r / min) on a magnetic stirrer for 30 min;

[0047] 2) Under stirring conditions, 0.228 g of thiourea was added to the mixed solution obtained in step 1), and then the mixture was stirred continuously (at a speed of 300 r / min) for 30 min until the mixture was uniformly mixed to obtain a reaction precursor solution;

[0048] 3) The reaction precursor solution obtained in step 2) was transferred to a polytetrafluoroethylene high-temperature reactor, and a hydrothermal reaction was carried out at 150° C. for 12 h. After the reaction was completed and cooled to room temperature, it was washed 4 times by water centrifugation (speed of 5000 r / min, time of 3 min), and then washed 4 times by anhydrous ethanol centrifugation (speed of 5000 r / min, time of 3 min), the product was collected, and dried at 60° C. for 12 h to obtain ZnS photocatalytic nanomaterials.

[0049] The XRD pattern of the ZnS photocatalytic nanomaterial prepared in this example is shown in Figure 1 As shown, from Figure 1 It can be seen from the figure that typical diffraction peaks of ZnS (111), (220), and (311) crystal planes appear at 2θ of 28.79°, 47.5°, and 56.3°, which is consistent with the ZnS (JCPDS No.05-0566) standard card. At the same time, the diffraction peaks are sharp and there are no impurity peaks, indicating that the prepared ZnS nanomaterials have high purity and crystallinity.

[0050] The SEM image of the ZnS photocatalytic nanomaterial prepared in this example is as follows: Figure 2 and Figure 3 As shown, from Figure 2 and Figure 3 As can be seen from the figure, the material has a unique three-dimensional structure, and the overall structure is a micron-spherical structure assembled by nanoparticles. This microstructure gives the ZnS material a larger specific surface area, which can provide more active sites and thus improve its catalytic activity.

[0051] Example 2

[0052] This embodiment provides a method for preparing a ZnS photocatalytic nanomaterial, and the specific steps are as follows:

[0053] 1) Obtaining a mixed solution: Under room temperature, weigh 0.658 g of zinc acetate dihydrate and 0.1 g of sodium tartrate, respectively, and dissolve them in 40 ml of an aqueous solution of triethylenetetramine (the volume ratio of water to triethylenetetramine is 2:1), and then stir them at a constant speed (300 r / min) on a magnetic stirrer for 30 min;

[0054] 2) Under stirring conditions, 0.228 g of thiourea was added to the mixed solution obtained in step 1), and then the mixture was stirred continuously (at a speed of 300 r / min) for 30 min until the mixture was uniformly mixed to obtain a reaction precursor solution;

[0055] 3) The reaction precursor solution obtained in step 2) was transferred to a polytetrafluoroethylene high-temperature reactor, and a hydrothermal reaction was carried out at 150° C. for 12 h. After the reaction was completed and cooled to room temperature, it was washed 4 times by water centrifugation (speed of 5000 r / min, time of 3 min), and then washed 4 times by anhydrous ethanol centrifugation (speed of 5000 r / min, time of 3 min), the product was collected, and dried at 60° C. for 12 h to obtain ZnS photocatalytic nanomaterials.

[0056] Example 3

[0057] This embodiment provides a method for preparing a ZnS photocatalytic nanomaterial, and the specific steps are as follows:

[0058] 1) Obtaining a mixed solution: Under room temperature, weigh 0.658 g of zinc acetate dihydrate and 0.1 g of sodium tartrate, respectively, and dissolve them in 40 ml of an aqueous solution of triethylenetetramine (the volume ratio of water to triethylenetetramine is 3:1), and then stir them at a constant speed (300 r / min) on a magnetic stirrer for 30 min;

[0059] 2) Under stirring conditions, 0.228 g of thiourea was added to the mixed solution obtained in step 1), and then the mixture was stirred continuously (at a speed of 300 r / min) for 30 min until the mixture was uniformly mixed to obtain a reaction precursor solution;

[0060] 3) The reaction precursor solution obtained in step 2) was transferred to a polytetrafluoroethylene high-temperature reactor, and a hydrothermal reaction was carried out at 130° C. for 12 h. After the reaction was completed and cooled to room temperature, it was washed 4 times by water centrifugation (speed of 5000 r / min, time of 3 min), and then washed 4 times by anhydrous ethanol centrifugation (speed of 5000 r / min, time of 3 min), the product was collected, and dried at 60° C. for 12 h to obtain ZnS photocatalytic nanomaterials.

[0061] Example 4

[0062] This embodiment provides a method for preparing a ZnS photocatalytic nanomaterial. The difference from Embodiment 1 is that sodium tartrate is not added to the mixed solution, and other conditions are the same as those in Embodiment 1.

[0063] Example 5

[0064] This embodiment provides a method for preparing a ZnS photocatalytic nanomaterial, which differs from Embodiment 1 in that, in step 1), zinc acetate dihydrate, sodium tartrate, triethylenetetramine and water are directly blended to obtain a mixed solution, and other conditions are the same as those in Embodiment 1.

[0065] Example 6

[0066] This embodiment provides a method for preparing a ZnS photocatalytic nanomaterial, and the specific steps are as follows:

[0067] 1) Obtaining a mixed solution: Under room temperature, weigh 0.8 g of zinc acetate dihydrate and 0.2 g of sodium tartrate, respectively, and dissolve them in 40 ml of an aqueous solution of triethylenetetramine (the volume ratio of water to triethylenetetramine is 3:1), and then stir them on a magnetic stirrer at a constant speed (speed of 500 r / min) for 20 min;

[0068] 2) Under stirring conditions, 0.278 g of thiourea was added to the mixed solution obtained in step 1), and then the mixture was stirred continuously (at a speed of 500 r / min) for 20 min until the mixture was uniformly mixed to obtain a reaction precursor solution;

[0069] 3) The reaction precursor solution obtained in step 2) was transferred to a polytetrafluoroethylene high-temperature reactor, and a hydrothermal reaction was carried out at 160° C. for 10 h. After the reaction was completed and cooled to room temperature, it was washed 6 times by water centrifugation (speed of 4000 r / min, time of 5 min), and then washed 6 times by anhydrous ethanol centrifugation (speed of 4000 r / min, time of 5 min), the product was collected, and dried at 70° C. for 12 h to obtain ZnS photocatalytic nanomaterials.

[0070] Example 7

[0071] This embodiment provides a method for preparing a ZnS photocatalytic nanomaterial, and the specific steps are as follows:

[0072] 1) Obtaining a mixed solution: Under room temperature, weigh 0.5 g of zinc acetate dihydrate and 0.05 g of sodium tartrate and dissolve them in 40 ml of an aqueous solution of triethylenetetramine (the volume ratio of water to triethylenetetramine is 3:1), and then stir the mixture on a magnetic stirrer at a constant speed (speed of 150 r / min) for 20 min;

[0073] 2) Under stirring conditions, 0.174 g of thiourea was added to the mixed solution obtained in step 1), and then the mixture was stirred continuously (at a speed of 150 r / min) for 40 min until the mixture was uniformly mixed to obtain a reaction precursor solution;

[0074] 3) The reaction precursor solution obtained in step 2) was transferred to a polytetrafluoroethylene high-temperature reactor, and a hydrothermal reaction was carried out at 150° C. for 14 h. After the reaction was completed and cooled to room temperature, it was washed 4 times by water centrifugation (speed of 6000 r / min, time of 2 min), and then washed 4 times by anhydrous ethanol centrifugation (speed of 6000 r / min, time of 2 min), the product was collected, and dried at 50° C. for 12 h to obtain ZnS photocatalytic nanomaterials.

[0075] Example 8

[0076] This embodiment provides a method for preparing a ZnS photocatalytic nanomaterial. The difference from Embodiment 1 is that in the mixed solution, the volume ratio of water to triethylenetetramine is 1:1, and other conditions are the same as those in Embodiment 1.

[0077] Example 9

[0078] This embodiment provides a method for preparing a ZnS photocatalytic nanomaterial. The difference from Embodiment 1 is that in the mixed solution, the volume ratio of water to triethylenetetramine is 4:1, and other conditions are the same as those in Embodiment 1.

[0079] Example 10

[0080] This embodiment provides a method for preparing a ZnS photocatalytic nanomaterial. The difference from Embodiment 1 is that the water in the mixed solution is replaced with a 25 vol% ethanol aqueous solution. Other conditions are the same as those in Embodiment 1.

[0081] Comparative Example 1

[0082] This comparative example provides a method for preparing a ZnS photocatalytic nanomaterial. The difference from Example 1 is that the triethylenetetramine in the mixed solution is replaced by ethylenediaminetetraacetic acid, and the other conditions are the same as Example 1.

[0083] Test Example 1

[0084] The degradation rate of tetracycline in water under sunlight irradiation of the ZnS photocatalytic nanomaterials and ZnS (commercially purchased, Aladdin Reagent Company) materials obtained in the above embodiments and comparative examples was tested. The test method is: 50 mg of ZnS photocatalytic nanomaterials are used to degrade an aqueous solution of tetracycline (volume 50 mL) with an initial concentration (C0) of 10 mg / L at room temperature and pressure, the light source is a 500W Xe lamp (simulated sunlight), and the degradation time is 300 min. The tetracycline concentration (C) is measured by a UV-visible spectrophotometer, and its degradation rate (C / C0) is calculated according to the concentration. In addition, in order to eliminate the influence of external interference factors, a group of experiments (i.e., tetracycline aqueous solution) without adding ZnS photocatalytic nanomaterials is set up as a blank control group. Among them, the test results of the ZnS photocatalytic nanomaterials and ZnS (commercially purchased) materials and the blank control group obtained in Example 1 are as follows Figure 4 shown.

[0085] The test results of each embodiment and comparative example, ZnS (commercially available) material, and blank control group are shown in Table 1 below.

[0086] Table 1

[0087]

[0088]

[0089] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.

Claims

1. A method for preparing a ZnS photocatalytic nanomaterial, characterized in that: include: obtaining a mixed solution of organic acid zinc salt, triethylenetetramine and solvent; The sulfur source is dissolved in the mixed solution to obtain a reaction precursor solution and a reaction is carried out to prepare the ZnS photocatalytic nanomaterial.

2. The preparation method according to claim 1, characterized in that: The organic acid zinc salt includes zinc acetate; and / or, the sulfur source comprises thiourea; And / or, the mixed solution also includes sodium tartrate; and / or, the volume ratio of the solvent to triethylenetetramine is (4-1):1, preferably (3-2):1; And / or, the solvent is water or an alcohol aqueous solution; preferably, the alcohol aqueous solution includes an ethanol aqueous solution; more preferably, the concentration of ethanol in the ethanol aqueous solution is ≤25 vol%.

3. The preparation method according to claim 2, characterized in that: Based on the total amount of triethylenetetramine and the solvent being 40 ml, the amount of sodium tartrate used is 0.05-0.2 g.

4. The preparation method according to claim 1, characterized in that: Based on the total amount of triethylenetetramine and solvent being 40 ml, the amount of the organic acid zinc salt is 0.5-0.8 g; And / or, the mass ratio of the organic acid zinc salt to the sulfur source is (0.5-0.8): (0.1-0.3); And / or, the process of obtaining the mixed solution includes: dissolving the organic acid zinc salt in a solution of triethylenetetramine and a solvent to obtain the mixed solution.

5. The preparation method according to claim 1, characterized in that: The reaction is a hydrothermal reaction or a solvothermal reaction; And / or, the reaction temperature is 130-160°C; And / or, the reaction duration is 10-14h; And / or, during the process of obtaining the mixed liquid, stirring is also performed; And / or, during the process of obtaining the reaction precursor solution, stirring is also performed; And / or, after the reaction, cooling, washing and drying are further performed.

6. The preparation method according to claim 5, characterized in that: The stirring speed is 150-500 r / min; And / or, the stirring treatment lasts for 20-40 minutes; And / or, during the washing process, water and anhydrous ethanol are respectively used for centrifugal washing 4-6 times; And / or, the drying temperature is 50-70°C; And / or, the duration of the drying treatment is ≥ 12 h.

7. The preparation method according to claim 6, characterized in that: The rotation speed of the centrifugal cleaning is 4000-6000r / min; And / or, the duration of the centrifugal washing is 2-5 min.

8. A ZnS photocatalytic nanomaterial, characterized in that: The photocatalytic nanomaterial is prepared by the method for preparing the ZnS photocatalytic nanomaterial described in any one of claims 1 to 7.

9. Use of the ZnS photocatalytic nanomaterial according to claim 8 in photocatalytic degradation of organic pollutants in water.

10. The use according to claim 9, characterized in that: The organic pollutant is an antibiotic; optionally, the antibiotic comprises tetracycline.

Citation Information

Patent Citations

  • Preparation method of visible light response zinc cadmium sulfur solid solution photocatalytic material

    CN106975521A

  • Method for preparing metal sulfide / amine-hybrid nanomaterials and metal sulfide nanomaterials

    CN107572581A

  • Preparation method of photocatalyst, photocatalyst and application of photocatalyst

    CN117299156A

  • Preparation method of monodisperse spherical zine sulfide nano particles

    CN1923702A

  • Cds-zns / go nanofibers and preparation method thereof

    WO2021072639A1